A DESCRIPTIVE STUDY ON NUTRITIONAL STATUS ASSESSMENT AND MORBIDITY PATTERN OF ADOLESCENTS (10–16 YEARS) RESIDING IN URBAN SLUMS OF AMRITSAR, PUNJAB - SINGH, JASMEET; MAHAJAN, SANJEEV; SS, DEEPTI; SINGH, TEJBIR; KUMARI, RUCHIKA; PADDA, PREETI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: To assess the nutritional status and morbidity pattern of adolescents age 10–16 years and to determine the various factors associated with under-nutrition. Methods: A descriptive cross-sectional study was conducted among 1600 households which were selected by systematic random sampling method from 64 slum areas. All adolescents aged 10–16 years were included. Required information was collected on a pretested performa. Height and weight were measured to assess their nutritional status and haemoglobin estimation was done by Sahli’s method. Descriptive statistics (frequencies and proportions) and univariate logistic regression were done to determine various factors associated with under nutrition. Results: Out of 603 study participants, 75% of adolescents were under-weight. About 82.3% had anemia. About 36% suffered from one or more infectious disease in the last 3 months. Going to school, occupation, female sex, and suffering from any infectious disease in the past 3 months were found to be associated with malnutrition. Addiction was reported in 9% of study participants. Conclusions: High prevalence of under-nutrition and anemia in our study reflects inequitable distribution of resources, low purchasing capacity of foods, and unequal food sharing patterns in families making them socially and biologically vulnerable.